2018
DOI: 10.3390/v10030133
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Defense and Innate Immune Memory in the Oyster

Abstract: The Pacific oyster, Crassostrea gigas, is becoming a valuable model for investigating antiviral defense in the Lophotrochozoa superphylum. In the past five years, improvements to laboratory-based experimental infection protocols using Ostreid herpesvirus I (OsHV-1) from naturally infected C. gigas combined with next-generation sequencing techniques has revealed that oysters have a complex antiviral response involving the activation of all major innate immune pathways. Experimental evidence indicates C. gigas u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 90 publications
1
53
0
Order By: Relevance
“…On the other hand, evidence for immune stimulation induced by repeated challenge with natural pathogens is available in clams and oysters (49)(50)(51)(52)(53)(54)(55). In the mussel M. galloprovincialis, increased bactericidal activity was observed after in vivo and subsequent in vitro challenge with Vibrio anguillarum (26).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, evidence for immune stimulation induced by repeated challenge with natural pathogens is available in clams and oysters (49)(50)(51)(52)(53)(54)(55). In the mussel M. galloprovincialis, increased bactericidal activity was observed after in vivo and subsequent in vitro challenge with Vibrio anguillarum (26).…”
Section: Discussionmentioning
confidence: 99%
“…The short time from recipient O. angasi exposure to first B. exitiosa infection may be caused by O. angasi having a lesser capacity to mount an effective immune response against B. exitiosa than other oyster species. Oysters lack immune memory homologous to vertebrates (Wang, Song, & Song, ) but display immune priming after exposure to a pathogen (Contreras‐Garduño et al, ; Little & Kraaijeveld, ), and the offspring of primed individuals can display increased immune capacity (Green & Speck, ). Ostrea edulis from B. ostreae ‐endemic areas have lower susceptibility to B. ostreae than O. edulis from B. ostreae ‐free areas (Culloty, Cronin, & Mulcahy, ), but it is unclear if this was due to immune priming or mass selection in wild populations for immune competence when exposed to B. ostreae .…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous immune priming experiments showed that Crassostrea gigas primed with poly(I:C) have improved survival to OsHV-1 infection (Green and Montagnani, 2013;Green et al, 2015b;Lafont et al, 2017), and this protection can be passed to the next generation (Green et al, 2016). Despite the physiological, metabolic and immunological response of C. gigas to OsHV-1 infection being well characterized (Corporeau et al, 2014;Green and Speck, 2018;Martenot et al, 2017;Tamayo et al, 2014;Young et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…OsHV-1 can cause 100 % mortality rate of C. gigas in less than one week (Paul-Pont et al, 2014), with the commercial production of C. gigas having now ceased entirely in several affected estuaries within Australia (Whittington et al, 2015). Urgency to mitigate the impacts of OsHV-1 has led to a closer examination of the antiviral responses of C. gigas to OsHV-1 infection (reviewed by Green and Speck, 2018). Observational studies suggest C. gigas are capable of adapting to OsHV-1 infection.…”
Section: Introductionmentioning
confidence: 99%